Social Conflict in the Short Story ‘Ad-Dalīlu At-Tāih (The Lost Guide)’ by Najib Kailani (A Sociological Study of Karl Marx) - Lutfiana, Rima; Dewi, Intan Sari (Diwan: Jurnal Bahasa dan Sastra Arab, 2023)
تحكي القصة القصيرة "الدليل التائه" في مختارات الكابوس لنجيب كيلاني عن حياة الشخصية الرئيسية التي تريد السعي وراء الشرف. الغرض من هذا البحث هو معرفة أشكال الصراع وأسبابه الاجتماعي في القصة القصيرة. الطريقة المستخدمة هي طريقة وصفية نوعية من خلال وصف البيانات التي تم العثور عليها. تشير نتائج هذه الدراسة إلى وجود شكلين فقط هما الصراع الشخصي والصراع بين الطبقات الاجتماعية. والصراع الشخصي يوجد إحدى عشرة بيانة وأما الصراع بين الطبقات الاجتماعية خمس بيانات. بينما لم يتم العثور على أشكال أخرى من الصراع مثل الصراع العنصري والصراع السياسي والصراع الدولي. أسباب الصراع الاجتماعي في القصة القصيرة عند نظرية كارل ماركس هو التغيير الاجتماعي والطبقة الاجتماعية والسلطة. وأما المشاكل أو المشكلات الاقتصادية التى تسبب الى تكوين الطبقتين و هما الطبقة العليا والطبقة الدنيا. Abstract The short story "Ad-Dalīlu at-Tāih" from Najib Kailani's anthology "Al-Kābūs" explores the search for dignity by its protagonist. This research aims to identify the forms and causes of social conflict within the story. Employing a descriptive qualitative method, the study analyzes relevant data. The findings reveal two primary forms of social conflict: personal conflicts and conflicts between social classes. Eleven instances of personal conflict and five of class conflict were identified, while other forms like racial, political, and international conflicts were absent. Drawing upon Karl Marx's theories, the study attributes the social conflict in the story to factors such as social change, class structure, and power dynamics. The emergence of economic disparity leads to the formation of two distinct classes: the upper and lower classes.